P392 Comprehensive video capsule endoscopy-based monitoring predicts short and long-term risk of disease flares in small bowel Crohn's disease: A prospective cohort study. (16th January 2018) - Ben-Horin, S; Lahat, A; Amitai, M M; Klang, E; Yablecovitch, D; Neuman, S; Levhar, N; Selinger, L; Bubis, M; Picard, O; Turner, D; Odes, S; et al.
Abstract: Background: The optimal monitoring strategy for predicting clinical deterioration in Crohn's disease (CD) patients remains undefined Methods: This was a prospective observational cohort study of patients with stable CD involving the small-bowel. Patients underwent magnetic resonance enterography (MRE) and ingested patency capsule. If patency was proved, patients were enrolled and underwent video capsule endoscopy (VCE) at baseline and every 6 months thereafter and bio-markers assessment every three months. CD treatment was unchanged during follow-up. Patients were followed for two years or until a clinical flare occurred, defined by a CDAI 70-points rise. Results: Of 89 patients undergoing MRE and patency capsule, 28 were excluded (non-patent small bowel n = 17, other causes n = 11). The included 61 patients swallowed a total of 231 VCEs over the 2-year study without complications or retentions. Overall, 17/61 (28%) of patients flared during 24 months. No clinical or demographic baseline parameter predicted a future flare. Baseline CRP modestly discriminated between patients with subsequent flares or not (AUC = 0.73, p < 0.001, hazard ratio 6.7, 95% CI 2.6–17.4). Baseline VCE Lewis score (LS) >350 for the worst SB tertile more strongly predicted future flares (AUC = 0.79, p < 0.0001, hazard ratio 10.7, 95% CI 3.8–30.3) and a cumulative LS < 450 performed similarly. Mucosal inflammation in the second tertile of the small-bowel correlated with future flares better than inflammation in either the first tertile or the distal third tertile. In contrast with VCE, baseline faecal calprotectin was not predictive (AUC = 0.63, p = 0.17, optimal cut-off value 160μg/g) and MRE indices were only weakly predictive of future flare. However, on a time-restricted analysis of all 425 serial measurements, the prediction-accuracy of calprotectin progressively increased from AUC = 0.62 for 24-months, through 0.67 for 12-months, 0.76 for 6-months and up to AUC = 0.81 for three-months' flare prediction. Time-restricted analysis for VCE also showed a stronger short-term 6 months prediction accuracy (AUC = 0.83, p < 0.0001). Patient tolerability of intensive small-bowel VCE monitoring was excellent. Conclusions: Calprotectin strongly predicts short-term (3 months) risk of flares in patients with small-bowel CD. In contrast, VCE accurately predicts both short-term but also long-term risk of disease exacerbation, and is safe and tolerable after small-bowel patency has been established. A worst-segment LS < 350 (or cumulative LS < 450) may be the clinically relevant target scores for small-bowel mucosal healing. A randomised controlled trial has been launched to investigate proactive interventional strategy based on this predictive algorithm.